Low-carbon synchronous grouting material based on shield muck and preparation method thereof
By adopting low-carbon synchronous grouting materials based on shield structure slag, the shortcomings of traditional synchronous grouting materials in early shear strength and later consolidation strength are solved, high-performance synchronous grouting materials are realized, and resource circulation is promoted. Utilization and low-carbon environmental protection.
Patent Information
- Application Number
- CN202411701818.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional tunnel synchronous grouting materials perform poorly in early shear strength and later consolidation strength, and are prone to plugging pipes, which cannot meet the needs of modern shield construction technology.
Using low-carbon synchronous grouting material based on shield slag, the material includes recycled stone powder, shield slag, sodium-based bentonite, curing agent and water reducing agent. Through specific mixing ratios and preparation methods, high-performance synchronization is formed. Grouting material.
It achieves excellent performance of early shear strength and later consolidation strength, is not easy to block pipes, does not contain cement, promotes the recycling of solid waste and shield waste soil resources, has low carbon emissions and low overall costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shield construction, and in particular to a low-carbon synchronous grouting material based on shield slag and a preparation method thereof. Background Art
[0002] With the rapid development of urban infrastructure, there will be more and more urban subways, railways, large-scale cross-river tunnels and other engineering projects. Shield tunnel technology is increasingly widely used in subways, tunnels and other projects due to its high safety, fast construction, economic and environmental protection, and good adaptability to the strata. However, the shield method also exposed some problems during the construction process. Synchronous grouting materials can fill the gaps around the shield tail and the segments, so that the surrounding rock and the segment lining form a whole, prevent the deformation of the strata and the floating of the segments, and ensure construction safety.
[0003] Traditional synchronous grouting materials include two categories: single-liquid inert slurry and hardenable slurry. Among them, single-liquid inert slurry cannot harden, and the overall stability of the tunnel segment lining is poor. This technology has been basically abandoned. Single-liquid hardenable slurry is a cementitious material added to the inert slurry, but its early shear strength is low and it is easy to clog the pipeline. With the continuous development of shield construction technology, hardenable technology can no longer meet the requirements of existing shield construction methods. The main grouting materials of traditional shear mortar technology are medium sand, fly ash and cement. Its defects such as long setting time, low late strength and high dependence on natural resources can no longer match the advanced shield technology, resulting in problems such as unsatisfactory grouting effect behind the tunnel shield lining structure wall. Summary of the invention
[0004] In order to overcome the defects of the prior art, a low-carbon synchronous grouting material based on shield slag and a preparation method thereof are provided to solve the problem of poor comprehensive performance of traditional tunnel synchronous grouting materials.
[0005] In order to achieve the above-mentioned purpose, a low-carbon synchronous grouting material based on shield slag is provided, comprising:
[0006] The invention comprises 200 to 380 parts by weight of regenerated stone powder, 100 to 200 parts by weight of mud, 24.8 to 30 parts by weight of sodium bentonite, 10 to 20 parts by weight of a curing agent, and 0.1 to 0.3 parts by weight of a water reducing agent;
[0007] The slurry includes shield slag and water, and the specific gravity of the slurry is 1.30-1.40 g / cm 3 The water content of the mud is between 60% and 70%, and the funnel viscosity of the mud is between 20 and 25 seconds.
[0008] Furthermore, the fineness modulus of the regenerated stone powder is 2.8 to 3.0.
[0009] Furthermore, the moisture content of the regenerated stone powder is between 8% and 10%.
[0010] Furthermore, the mass fraction of particles larger than 5 mm in the regenerated stone powder is less than 3%.
[0011] Furthermore, the water reducer is a polycarboxylate water reducer.
[0012] Furthermore, it comprises 360 parts by mass of recycled stone powder, 200 parts by mass of mud, 29 parts by mass of sodium bentonite, 20 parts by mass of curing agent, and 0.1 parts by mass of water reducing agent, and the shield slag is silty clay.
[0013] Furthermore, it comprises 380 parts by mass of recycled stone powder, 200 parts by mass of mud, 30 parts by mass of sodium bentonite, 20 parts by mass of curing agent, and 0.3 parts by mass of water reducing agent, and the shield slag is silty clay.
[0014] Furthermore, it comprises 200 parts by mass of regenerated stone powder, 100 parts by mass of mud, 24.8 parts by mass of sodium bentonite, 10 parts by mass of a curing agent, and 0.1 parts by mass of a water reducing agent, and the shield slag is sandy silt.
[0015] The present invention provides a method for preparing a low-carbon synchronous grouting material based on shield slag, comprising the following steps:
[0016] Obtain the moisture content of shield slag;
[0017] Based on the water content of the shield slag, water is added to the shield slag and stirred evenly to obtain mud, the specific gravity of the mud is 1.30-1.40 g / cm 3 , the water content of the mud is 60% to 70%, and the funnel viscosity of the mud is 20 to 25s;
[0018] Adding sodium bentonite into water and stirring evenly to obtain bentonite slurry, wherein the mass ratio of the sodium bentonite to the water is 6%;
[0019] Adding regenerated stone powder, curing agent and bentonite slurry into the mud and stirring evenly to obtain a mixed slurry;
[0020] The water reducing agent is added into the mixed slurry and stirred evenly to obtain a low-carbon synchronous grouting material.
[0021] The beneficial effect of the present invention is that the low-carbon synchronous grouting material based on shield slag of the present invention adopts solid waste recycled resources and shield slag as the main raw materials to prepare low-carbon and high-performance synchronous grouting materials, which are characterized by excellent early shear strength, excellent later consolidation strength, not easy to block pipes, and does not contain cement, thereby maximizing the recycling of resources such as solid waste and shield spoil, with low carbon emissions and low overall cost.
[0022] The main raw materials of the low-carbon synchronous grouting material based on shield slag of the present invention are recycled stone powder and shield slag, and the proportion of recycled resources in the mix ratio exceeds 90%, which can maximize the recycling of urban solid waste resources. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention.
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.
[0025] The invention provides a low-carbon synchronous grouting material based on shield slag, comprising 200-380 parts by mass of regenerated stone powder, 100-200 parts by mass of mud, 24.8-30 parts by mass of sodium-based bentonite, 10-20 parts by mass of a curing agent, and 0.1-0.3 parts by mass of a water reducing agent.
[0026] The slurry includes shield slag and water. Shield slag can be replaced by shield abandoned slurry. The specific gravity of the slurry is 1.30~1.40g / cm 3 The water content of the mud is 60% to 70%. The funnel viscosity of the mud is 20 to 25 seconds.
[0027] The fineness modulus of recycled stone powder is 2.8-3.0.
[0028] The moisture content of recycled stone powder is between 8% and 10%.
[0029] The mass fraction of particles larger than 5 mm in the regenerated stone powder is less than 3%.
[0030] The water reducing agent is a polycarboxylic acid water reducing agent.
[0031] As a preferred embodiment, the low-carbon synchronous grouting material based on shield slag of the present invention comprises 360 parts by mass of regenerated stone powder, 200 parts by mass of mud, 29 parts by mass of sodium-based bentonite, 20 parts by mass of curing agent, and 0.1 parts by mass of water reducing agent. The shield slag is silty clay.
[0032] As a preferred embodiment, the low-carbon synchronous grouting material based on shield slag of the present invention comprises 380 parts by mass of recycled stone powder, 200 parts by mass of mud, 30 parts by mass of sodium-based bentonite, 20 parts by mass of curing agent, and 0.3 parts by mass of water reducing agent. The shield slag is silty clay.
[0033] As a preferred embodiment, the low-carbon synchronous grouting material based on shield slag of the present invention comprises 200 parts by mass of regenerated stone powder, 100 parts by mass of mud, 24.8 parts by mass of sodium-based bentonite, 10 parts by mass of curing agent, and 0.1 parts by mass of water reducing agent. The shield slag is sandy silt.
[0034] The present invention provides a method for preparing a low-carbon synchronous grouting material based on shield slag, comprising the following steps:
[0035] S1. Obtain the moisture content of shield slag.
[0036] S2. Based on the moisture content of shield slag, add water to the shield slag and stir evenly to obtain mud. The specific gravity of the mud is 1.30-1.40g / cm 3 The water content of the mud is between 60% and 70%, and the funnel viscosity of the mud is between 20 and 25s.
[0037] When the shield slag is sandy silt, the prepared mud has a specific gravity of 1.30-1.40 g / cm 3 , water content is between 66% and 68%, and funnel viscosity is between 20 and 22s.
[0038] S3. Add sodium bentonite into water and stir evenly to obtain bentonite slurry, wherein the mass ratio of sodium bentonite to water is 6%.
[0039] Specifically, sodium bentonite is added into water and allowed to stand for a preset time, and then stirred evenly to obtain bentonite slurry.
[0040] In this embodiment, the preset time is 24 hours. The mass ratio of sodium bentonite to water is 6%.
[0041] S4. Add the regenerated stone powder, curing agent and bentonite slurry into the mud and stir evenly to obtain a mixed slurry.
[0042] Specifically, the stone powder, curing agent, bentonite slurry and mud are mixed and stirred evenly according to the proportion, stirred at a low speed of 50-80 r / min for 4-5 minutes, and then stirred at a high speed of 150-200 r / min for 2-3 minutes to form a mixed slurry.
[0043] In this embodiment, the regenerated stone powder is a fine particle material obtained by crushing, screening and grinding construction waste such as engineering waste, demolition waste and decoration waste. Construction waste mainly includes concrete, bricks, tiles, stones and the like.
[0044] The curing agent is a new type of cementitious material specially used for soft soil reinforcement. It is cement-free, purely mineral-based, and prepared from bulk industrial solid waste materials. It does not require high-temperature calcination in production and is a low-energy, green and low-carbon building material. It is in the form of off-white powder. After being fully mixed with the soil (mud), it undergoes physical and chemical reactions with the soil (mud). Compared with traditional silicate cement, the 28d strength of the reinforced soil is 20% to 100% higher than the 28d strength of cement soil. The solidified body meets environmental standards and maintains long-term stability. Its relevant performance meets the Shanghai local standard "Technical Standard for the Application of Soil Hardeners" (DG_TJ08-2082-2023).
[0045] In this embodiment, the curing agent is a 1.0 grade common curing agent produced by Shanghai Zhuzhao New Material Technology Co., Ltd.
[0046] S5. Add the water reducing agent into the mixed slurry and stir evenly to obtain a low-carbon synchronous grouting material.
[0047] Add the water reducing agent into the mixed slurry, stir evenly, and obtain a low-carbon synchronous grouting material.
[0048] Low-carbon synchronous grouting material has good working performance and mechanical properties. Its initial slump is 120-160mm, 24h slump is greater than 40mm, and the bulk density is 1850-1900kg / m 3 , pressure water seepage rate is less than 5%, initial shear strength is greater than 800Pa, 8h shear strength is greater than 1200Pa, 24h shear strength is greater than 1900Pa, 7d compressive strength is greater than 0.3Mpa, 28d compressive strength is greater than 0.8Mpa, and the setting time is about 2d.
[0049] The low-carbon synchronous grouting material based on shield slag of the present invention adopts solid waste recycled resources and shield abandoned soil (slurry) as main raw materials to prepare low-carbon and high-performance synchronous grouting materials. The low-carbon synchronous grouting material has the characteristics of excellent early shear strength, excellent later consolidation strength, not easy to block pipes, and does not contain cement, thereby maximizing the recycling of resources such as solid waste and shield abandoned soil, with low carbon emissions and low overall cost.
[0050] The main raw materials of the low-carbon synchronous grouting material based on shield slag of the present invention are recycled stone powder and shield slag (mud), and the proportion of recycled resources in the mix ratio exceeds 90%, which can maximize the recycling of urban solid waste resources.
[0051] The curing agent used in the low-carbon synchronous grouting material based on shield slag of the present invention is a low-energy consumption, low-carbon soil hardener, and its usage in the mix ratio is less than 4%, which can achieve good mechanical properties.
[0052] The low-carbon synchronous grouting material based on shield slag of the present invention uses recycled stone powder as aggregate and a low-carbon and low-energy soil solidifier as a gel material to prepare the synchronous grouting material, which can simultaneously obtain high early shear strength and high late compressive strength, that is, it is beneficial to tunnel anti-floating in the early stage and beneficial to tunnel stability in the later stage.
[0053] The low-carbon synchronous grouting material based on shield slag of the present invention is based on the concept of recycling renewable resources, uses shield abandoned soil or mud, stone powder as main raw materials, low-carbon curing agent as auxiliary material, and functional regulating admixtures to prepare a low-carbon and high-performance synchronous grouting material.
[0054] The low-carbon synchronous grouting material based on shield slag of the present invention uses recycled stone powder and shield slag (abandoned slurry) as the main raw materials, which can not only reduce the dependence on natural sand, but also turn waste into treasure and solve the disposal problem of abandoned soil or abandoned slurry. Secondly, the low-carbon synchronous grouting material based on shield slag of the present invention does not use cement as a gelling material, which can greatly reduce carbon emissions. The curing agent prepared with solid waste as raw materials can also realize the recycling of solid waste resources.
[0055] In terms of performance, the low-carbon synchronous grouting material based on shield slag of the present invention has both early shear strength and late compressive strength. Therefore, the low-carbon synchronous grouting material based on shield slag of the present invention can solve the shortcomings of existing shear-resistant synchronous grouting materials.
[0056] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.
Claims
1. A low-carbon synchronous grouting material based on shield slag, characterized in that: The invention comprises 200 to 380 parts by weight of regenerated stone powder, 100 to 200 parts by weight of mud, 24.8 to 30 parts by weight of sodium bentonite, 10 to 20 parts by weight of a curing agent, and 0.1 to 0.3 parts by weight of a water reducing agent; The slurry includes shield slag and water, and the specific gravity of the slurry is 1.30-1.40 g / cm 3 The water content of the mud is between 60% and 70%, and the funnel viscosity of the mud is between 20 and 25 seconds.
2. The low-carbon synchronous grouting material based on shield slag according to claim 1 is characterized in that: The fineness modulus of the regenerated stone powder is 2.8-3.
0.
3. The low-carbon synchronous grouting material based on shield slag according to claim 2 is characterized in that: The moisture content of the regenerated stone powder is between 8% and 10%.
4. The low-carbon synchronous grouting material based on shield slag according to claim 3 is characterized in that: The mass fraction of particles exceeding 5 mm in the regenerated stone powder is less than 3%.
5. The low-carbon synchronous grouting material based on shield slag according to claim 1 is characterized in that: The water reducer is a polycarboxylate water reducer.
6. The low-carbon synchronous grouting material based on shield slag according to claim 1, characterized in that: It comprises 360 parts by mass of recycled stone powder, 200 parts by mass of mud, 29 parts by mass of sodium bentonite, 20 parts by mass of curing agent, and 0.1 parts by mass of water reducing agent, and the shield slag is silty clay.
7. The low-carbon synchronous grouting material based on shield slag according to claim 1, characterized in that: It comprises 380 parts by mass of regenerated stone powder, 200 parts by mass of mud, 30 parts by mass of sodium-based bentonite, 20 parts by mass of curing agent, and 0.3 parts by mass of water reducing agent, and the shield slag is silty clay.
8. The low-carbon synchronous grouting material based on shield slag according to claim 1, characterized in that: It comprises 200 parts by mass of regenerated stone powder, 100 parts by mass of mud, 24.8 parts by mass of sodium-based bentonite, 10 parts by mass of a curing agent, and 0.1 parts by mass of a water reducing agent, and the shield slag is sandy silt.
9. A method for preparing low-carbon synchronous grouting material based on shield slag as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Obtain the moisture content of shield slag; Based on the water content of the shield slag, water is added to the shield slag and stirred evenly to obtain mud, the specific gravity of the mud is 1.30-1.40 g / cm 3 , the water content of the mud is 60% to 70%, and the funnel viscosity of the mud is 20 to 25s; Adding sodium bentonite into water and stirring evenly to obtain bentonite slurry, wherein the mass ratio of the sodium bentonite to the water is 6%; Adding regenerated stone powder, curing agent and bentonite slurry into the mud and stirring evenly to obtain a mixed slurry; The water reducing agent is added into the mixed slurry and stirred evenly to obtain a low-carbon synchronous grouting material.